2015
DOI: 10.1055/s-0034-1398531
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced Natural Killer Cell Activation is Driven by Epigenetic Modifications

Abstract: Exercise has been proven to reduce the risk and progression of various diseases, such as cancer, diabetes and neurodegenerative disorders. Increasing evidence suggests that exercise affects the cytokine profile and changes distribution and function of tumor-competitive immune cells. Initial studies have shown that different exercise interventions are associated with epigenetic modifications in different tissues and cell types, such as muscle, fat, brain and blood. The present investigation examines the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Both authors independently reviewed the full-text articles and determined that 36 studies were not eligible for review for the following reasons: study was not published in English (n=1), no full-text was available (n=12), no control group (n=3), no PA intervention (n=6), multiple program features (n=1), protocol article (n=2), no health and/or QOL outcome reported (n=1), and age criteria not met (n=10). For those studies that were excluded because of the age criteria, participants were either above the defined age range [48-55] or samples were comprised of ≤50% adolescents [56,57]. This left 2 articles that met the predetermined eligibility criteria [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Both authors independently reviewed the full-text articles and determined that 36 studies were not eligible for review for the following reasons: study was not published in English (n=1), no full-text was available (n=12), no control group (n=3), no PA intervention (n=6), multiple program features (n=1), protocol article (n=2), no health and/or QOL outcome reported (n=1), and age criteria not met (n=10). For those studies that were excluded because of the age criteria, participants were either above the defined age range [48-55] or samples were comprised of ≤50% adolescents [56,57]. This left 2 articles that met the predetermined eligibility criteria [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, two studies demonstrated an increase in the CD56 dim CD16 bright NK cell subset, other studies demonstrated a higher frequency of the CD56 bright CD16 dim/neg NK cell subpopulation (86,203,209,210). However, physical activity increased the expression of the activating NK cell receptors CD69 and NKG2D and the degranulation marker CD107a as well as the IFN-γ, perforin, and granzyme B content of NK cells (73,196,203,211). Furthermore, the expression of the inhibitory NK cell receptor KLRG1 was reduced after exercise training (203).…”
Section: Reactivation Of Nk Cells By Body Weight Reduction and Physicmentioning
confidence: 97%
“…Recently, Zimmer et al. (, ) found increases in histone acetylation and DNA methylation with endurance exercise, and found an up‐regulation of gene transcription for NK cell activation receptors. Acute exercise bouts can increase the expression of the killer‐cell immunoglobulin‐like receptor (KIR) gene (Maltseva et al.…”
Section: Discussionmentioning
confidence: 99%